MACC1 revisited - an in-depth review of a master of metastasis - Paul Curtis Schöpe; Sebastian Torke; Dennis Kobelt; Benedikt Kortüm; Christoph Treese; Malti Dumbani; Nazli Güllü; Wolfgang Walther; Ulrike Stein (BMC, 2024)
Abstract Cancer metastasis remains the most lethal characteristic of tumors mediating the majority of cancer-related deaths. Identifying key molecules responsible for metastasis, understanding their biological functions and therapeutically targeting these molecules is therefore of tremendous value. Metastasis Associated in Colon Cancer 1 (MACC1), a gene first described in 2009, is such a key driver of metastatic processes, initiating cellular proliferation, migration, invasion, and metastasis in vitro and in vivo. Since its discovery, the value of MACC1 as a prognostic biomarker has been confirmed in over 20 cancer entities. Additionally, several therapeutic strategies targeting MACC1 and its pro-metastatic functions have been developed. In this review, we will provide a comprehensive overview on MACC1, from its clinical relevance, towards its structure and role in signaling cascades as well as molecular networks. We will highlight specific biological consequences of MACC1 expression, such as an increase in stem cell properties, its immune-modulatory effects and induced therapy resistance. Lastly, we will explore various strategies interfering with MACC1 expression and/or its functions. Conclusively, this review underlines the importance of understanding the role of individual molecules in mediating metastasis.